Aims to Reduce Coercive Measures in Forensic Inpatient Treatment: A 9-Year Observational Study - Lau, Steffen; Brackmann, Nathalie; Mokros, Andreas; Habermeyer, Elmar (Frontiers in Psychiatry, 2020)
Protecting the human rights is particularly important within the forensic context because patients in forensic psychiatric institutions are not admitted voluntarily and so the treatment itself is of coercive nature. Coercive measures (i.e., actions against the will of the patient such as forced medication, seclusion or restraint) form an additional incision of personal rights. Although the use of coercion within forensic psychiatric institutions remains controversial, little empirical research has been conducted on the use of coercive measures within forensic settings. The study presented here can contribute to close this research gap. National and international organizations on the prevention of torture or inhuman or degrading treatment have emphasized the need to keep the incidents of coercive measures to a minimum. Criticism by such organizations on high rates of seclusion, restraint and compulsory medication have led to organizational changes within the present institution which is Switzerland’s largest forensic clinic with an average of 124 patients per year. After a first visit of such a committee, e.g. the detailed documentation of coercive measures became obligatory and part of special reports. Changes in the use of coercive measures are presented here. Data on coercive measures was analyzed for years 2010 to 2018. In respect to the most invasive coercive measurement, restraint, a minimum of four patients in 2017 and a maximum of 14 patients in 2010 have been subject to this form of coercive measurement. A minimum of sixteen patients in 2012 to a maximum of 40 patients in 2010 were secluded. Though total number and duration show a trend towards a reduction in severity of coercive measures on average, a few patients are not responsive to deescalating interventions. Preventive mechanisms, documentation standards and efforts to ensure humane and adequate treatment are discussed under ethical considerations of coercive measures within court mandated treatment.